Revitalizing Critical Thinking in Acehnese Society: A Cultural and Islamic Framework - Asmanidar, Asmanidar (Program Studi Aqidah dan Filsafat Islam, 2024)
Critical thinking is a vital skill for developing adaptive societies capable of addressing the complexities of globalization and digitalization. In Aceh, however, critical thinking has significantly declined, as evidenced by the uncritical acceptance of unverified information, the prevalence of stereotypes, and decisions driven by conformity and egocentrism. This study investigates the root causes of this stagnation and proposes strategies for revitalization by integrating Islamic epistemology and Acehnese cultural values. Using a qualitative phenomenological approach, data were collected through semi-structured interviews, participatory observations, and document analysis involving 15 informants, including educators, community leaders, and youth in Neusu Aceh. The findings highlight five key barriers to critical thinking: egocentrism, self-interested thinking, conformity, unfounded assumptions, and stereotypes. These challenges are exacerbated by low digital literacy and cultural norms that prioritize group harmony over individual reflection. Drawing on Al-Ghazali’s tazkiyyat al-nafs (purification of the soul) and Kant’s sapere aude (dare to think independently), this study emphasizes the need for intellectual humility, courage, empathy, integrity, and rationality to combat these issues. The proposed strategies include integrating reflective practices into formal and non-formal education, promoting digital literacy programs tailored to local needs, and leveraging Acehnese Islamic traditions to foster a culture of critical thinking.